The Reality of Human Talent Management in Algerian Higher Education Institutions: Field Study at Mohamed Khider - Biskra University - Selikh, Houria; Grichi, Mohamed (The Arab Journal of Administration, 2020)
The aim of this Study is to identify the perceptions of the respondents about the level of availability of talent management in various dimensions at Biskra University. To reach this, a major hypothesis and four sub-hypotheses were formulated and it is tested by using a one sample T-test. Besides, the statistical analysis of the data was also used in other methods such as descriptive statistical measures (Mean and Standard Deviation). The questionnaire was used as a crucial tool for collecting data from the study sample of (99) workers. The study came to a number of results, the most important of which is that the Biskra University’s level of interest in human talent management with their different dimensions at was average according to the study scale in which the Mean of the responses of the individuals in the research sample for this variable as in total (2.83). Furthermore, the study led to a number of recommendations: The university should use multiple and objective methods of selecting individuals so as to match the efficiency of the individual with the job vacancy. It should also revive the spirit of competition between the workers so as to work on self-development in leadership positions that are important and appropriate to their abilities. And sensitizing the talent individuals to the achievement in the field of their jobs and to back up discussion among them so as to invest their intellectual potential and strengthen their loyalty to it.